2009
DOI: 10.1902/jop.2009.080600
|View full text |Cite
|
Sign up to set email alerts
|

A Surgical Reentry Study on the Influence of Platelet‐Rich Plasma in Enhancing the Regenerative Effects of Bovine Porous Bone Mineral and Guided Tissue Regeneration in the Treatment of Intrabony Defects in Humans

Abstract: Within the limitations related to using a small sample size, PRP did not significantly augment the effects of BPBM and GTR in promoting the clinical resolution of intrabony defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…However, comparison between the two groups revealed no statistically significant difference in the reduction of radiographic defect depth or the defect fill when measured at 6 and 9 months respectively. The results of this inter group comparison were found to be similar to the results of previously conducted studies by Camargo PM et al, (2009) [40] and Saini N et al, (2011) [35], where they found significant improvement in the test sites as compared to control sites in defect depth reduction and bone fill. Significant improvement in clinical and radiological parameters both at test and control sites may also be attributed to the physical characteristic of the regenerative materials used.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, comparison between the two groups revealed no statistically significant difference in the reduction of radiographic defect depth or the defect fill when measured at 6 and 9 months respectively. The results of this inter group comparison were found to be similar to the results of previously conducted studies by Camargo PM et al, (2009) [40] and Saini N et al, (2011) [35], where they found significant improvement in the test sites as compared to control sites in defect depth reduction and bone fill. Significant improvement in clinical and radiological parameters both at test and control sites may also be attributed to the physical characteristic of the regenerative materials used.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results on comparison between two groups were obtained in previous studies [23,24,[31][32][33][34], but contradictory results were found by Saini N et al, (2011), where there was significant reduction in PPD in test group compared to control group [35].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The activity of a bioactive glass graft material (Demir et al 2007), of a b-tricalcium phosphate graft (Dori et al 2008) as well as of a bovine porous bone mineral graft with and without a membrane barrier (Camargo et al 2009) has not been positively influenced by the presence of PRP.…”
Section: Discussionmentioning
confidence: 99%
“…Acceleration of hard tissue maturation and block graft procedures also produces a quantity of immature hard osteoid tissue within lesser time than the conventional time, hence improves primary stability for implant along with 20% greater trabecular bone density and 85% greater proportion of mature haversian system in the initial months supported by no evidence of active resorption and remodeling, indicating a level of stable maturity. 8,32 The main purpose of PRP is to reduce the use of autologous bone graft collected from the patients sites and reducing the mucosal incisions 32 Though Ozdemir, Raghoebar, Schaaf et al conveyed no beneficial effects of PRP with grafts in their literature [33][34][35][36][37][38][39][40][41][42][43] (Table 2).…”
Section: Marx Et Al Supported By Garg Et Al 2004mentioning
confidence: 99%